Multidisciplinary surgical approach in the treatment of giant mucinous ovarian cystadenocarcinoma - Ćurčić, Jelena; Golijan, Borislav; Nikolić, Jelena; Stajić, Dragan; Ćurčić, Aleksandar (Archive of Oncology, 2026)
Introduction: Giant ovarian tumors (>20 cm) are not common and often present late, with organ compression symptoms and increased abdominal girth. Early diagnosis is challenging due to nonspecific complaints until tumors reach massive dimensions. Case Presentation: A 49‑year‑old woman presented with progressive abdominal distension over, as she claimed, four months, culminating in a 180-cm abdominal circumference that impaired mobility and caused orthopnea. Contrast‑enhanced CT demonstrated a 54 × 26 × 25 cm cystic mass of ovarian origin, with focal wall thickening up to 5.6 cm, displacing abdominopelvic organs and elevating diaphragm. After multidisciplinary consultation, a midline laparotomy was performed. Controlled puncture and aspiration yielded approximately 53 L of mucinous fluid. A right adnexectomy was performed, and frozen‑section analysis indicated a borderline mucinous tumor. The operation continued with total hysterectomy, left adnexectomy, and partial omentectomy. Abdominal closure was achieved by abdominal and plastic surgeons: excess fascia and skin were excised, a synthetic mesh was placed, and abdominoplasty was performed. Definitive histopathology and immunohistochemistry confirmed right ovary mucinous cystadenocarcinoma without capsular surface involvement or lymphovascular invasion, staged as FIGO IC1. The patient received six cycles of adjuvant paclitaxel–carboplatin. At one‑year follow‑up, the patient exhibited no evidence of recurrence and satisfactory abdominal contour. Conclusion: Management of giant ovarian tumors demands meticulous preoperative planning and a coordinated multidisciplinary team. Surgical challenges include safe tumor decompression, accurate intraoperative diagnosis, and specialized abdominal wall reconstruction including gynecologic, abdominal, and plastic surgical expertise. Keywords: giant ovarian tumors, borderline ovarian tumor, mucinous cystadenocarcinoma.